Sustainability in Business: A Strategic Tool for Long-Term Growth - Al-Shaibani, Ebrahim Marwan Ahmed Ahmed; Ashidiqy, Abu Bakar; Putra, Bonse Aris Mandala (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Sustainability has emerged as a defining principle of modern business strategy, shaping how organizations compete, innovate, and grow in an increasingly uncertain world. This paper investigates sustainability as a strategic instrument for achieving long-term organizational growth through environmental, social, and governance (ESG) integration. Using a qualitative multi-case approach involving Unilever, IKEA, and Tesla, this study identifies key mechanisms linking sustainability with innovation, stakeholder trust, and resilience. Findings reveal that firms embedding sustainability in strategic decision-making outperform peers in profitability, adaptability, and brand reputation. The paper concludes that sustainability is no longer optional—it is the foundation of enduring competitiveness in the twenty-first century.